2002
DOI: 10.1002/jcb.10143
|View full text |Cite
|
Sign up to set email alerts
|

Smoothelin contains a novel actin cytoskeleton localization sequence with similarity to troponin T

Abstract: Smoothelin, a cytoskeletal protein, exists in a large isoform specifically expressed in vascular smooth muscle cells, and a small visceral isoform generated by a downstream transcriptional start site. Using fusions to the green fluorescent protein, we could show that both smoothelin isoforms are localized at actin containing filaments and mapped two domains that are each sufficient for localization at the actin cytoskeleton. The first domain is located in the vascular-specific, N-terminal half of smoothelin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…Instead, smooth muscle tropomyosin interacts with h-caldesmon and SM-calponin, which partly take over the role of troponins. 5 Importantly, smoothelins contain a 37-amino acid sequence that is similar to the tail domain of troponin T. 10 In skeletal muscle, this domain not only is required for troponin T interaction with tropomyosin but also is involved in the activation of actomyosin ATPase. 27 Thus, smoothelins might be part of a smooth muscle tropomyosintroponin-like system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, smooth muscle tropomyosin interacts with h-caldesmon and SM-calponin, which partly take over the role of troponins. 5 Importantly, smoothelins contain a 37-amino acid sequence that is similar to the tail domain of troponin T. 10 In skeletal muscle, this domain not only is required for troponin T interaction with tropomyosin but also is involved in the activation of actomyosin ATPase. 27 Thus, smoothelins might be part of a smooth muscle tropomyosintroponin-like system.…”
Section: Discussionmentioning
confidence: 99%
“…6 -9 They are encoded by a single-copy gene that generates 2 major isoforms, both containing a troponin T-like domain. 10 The smaller smoothelin-A isoform is expressed most prominently in visceral SMCs. In contrast, the 110-kDa smoothelin-B, which is encoded by the smoothelin-A exons plus 10 upstream exons, is found only in vascular SMCs.…”
Section: Clinical Perspective P 836mentioning
confidence: 99%
“…Two isoforms of smoothelin have been identified: a 59 kDa isoform (smoothelin A) that is expressed in visceral smooth muscle such as intestine [33] and a 100 kDa isoform (smoothelin B) that is expressed in vascular smooth muscle [34]. More recently, Leonhart and colleagues [36] have defined two alternate splice variants that contain spectrin family similarity. In this report, we present an additional member of the smoothelin family of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that two CH-domains in tandem are required for actinbinding (reviewed in [41]). The smoothelins possess novel actin binding domains that are responsible for association with actin containing filaments [36]. The large vascular specific smoothelin isoform contains two actin binding domains, whereas the small visceral specific isoform contains only one actin binding domain (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation